FINANCIAL PERFORMANCE ANALYSIS OF BANK SULUT USING DUPONT SYSTEM, YEAR 2009-2012. - Kojoh, Riska Margarit (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Bank Sulut is the only one of the regional bank in North Sulawesi. Regional bank is known as its own regional economy growth agency. Financial performance analysis is important to set company plans and decision in order to achieve their goals. This research analyze the financial performance of bank Sulut for the period 2009-2012 by using the DuPont system based on analysis of return on equity and return on investment model. Theories supporting research are financial performance and financial statement. The population of this research is all financial statement of Bank Sulut from year 1961 until year 2012. The sample of this research is Bank Sulut audited financial statement from 2009-2012 that have been issued.It was found that the financial performance of Bank Sulut is good in the term of return on equity and return on investment. Bank Sulut financial performance can generally stated as good performance. Profitability ratios of Bank Sulut show the ability of the bank to increase profit, so the net income can cover the expenses cost. Bank Sulut management needs to pay attention closely to cash management in order to keep cash rate above the regulation and have to increase interest income with controlled expenses to increase both shareholder investment and company investment. Keywords: financial performance, financial statement